A new species of Blakea (Blakeeae, Melastomataceae) from Ecuador - Fernández-Fernández, Diana; Ulloa Ulloa, Carmen; Penneys, Darin S. (Phytotaxa, 2016)
A new species, Blakea nangaritzana D. Fernández, C. Ulloa & Penneys from Nangaritza canton, Zamora-Chinchipe, southern Ecuador is described and illustrated. It differs from all other species of the genus by the character combination of terrestrial trees up to 25 m tall, outer and inner floral bracts free, narrowly oblanceolate to linear, hypanthium ca. 7 × 8 mm, and calyx lobes 4–5 mm long.